HUBUNGAN TINGKAT KECEMASAN, PENDIDIKAN, DAN PEKERJAAN DENGAN PEMILIHAN ALAT KONTRASEPSI IUD DI DESA GUNUNG MERAKSA - Dian Selina; Amlah Amlah; Reffi Dhamayanti; Desmansyah Desmansyah (Jurnal Ilmu Kebidanan, 2023)
Intra Uterine Device or commonly known as IUD is a contraceptive in the form of a small, silastic, with a sleeve or copper wire around it that is installed in the uterus which provides long-term protection against pregnancy. The purpose of this study was to find out the relationship between anxiety levels, education, and work with the choice of IUD contraception in Gunung Meraksa Village, Lubuk Batang OKU District in 2023. This type of research was an analytic observational study with a cross sectional design or approach. The population in this study were all active family planning acceptors, totaling 385 respondents, the total sample being 80 respondents. The type of data uses primary data, the dependent variable is the selection of IUD contraception, the independent variables are anxiety level, education, and occupation. The results of bivariate research on the relationship between anxiety levels, education, and employment with the choice of IUD contraception based on the chi square statistical test anxiety level p-value 0.000 <0.05, education p-value 0.000 <0.05 and employment p-value 0.000 <0, 05 it can be concluded that there is a relationship between anxiety levels, education, and work with the selection of IUD contraception in Gunung Meraksa Village, Lubuk Batang District OKU in 2023. As for suggestions for village midwives in Gunung Meraksa village, it is expected that health workers/staff conduct education regarding IUD contraception both physically and face to face or with media that can be accessed.